Проблемы качества электроэнергии в сетях 330-750 кВ ГП НЭК "Укрэнерго" - Бородин, Д. В.; Гриб, Олег Герасимович; Сапрыка, Александр Викторович (Донецкий национальный технический университет, 2008)
The paper deals with quality of electrical energy in the system power networks in Ukraine of 330-750 kV. An analysis of measurements results has been done. The results may be used for creating new standards of power quality and building automated systems of power quality control.
Keywords: потери энергетические; анализатор микропроцессорный; напряжение; сеть системообразующая